Book review. COVID-19 in Italy Social Behavior and Governmental Policies, by Lucia Velotti, Gabriella Punziano, Felice Addeo, Routledge, London 2022 - Ferdinando Iazzetta (Culture e Studi del Sociale)
The book, edited by Lucia Velotti, Gabriella Punziano and Felice Addeo illustrates and examines people's perception of risk, their willingness to trust the sources and channels of information available to them and their attitudes towards protective behaviors by analyzing different aspects of the Protective Action Decision Model (PADM) during the COVID-19 pandemic in Italy.